Pars Pro Toto: Every Single Cell Matters - Christiaens, Fien; Canher, Balkan; Lanssens, Fien; Bisht, Anchal; Stael, Simon; De Veylder, Lieven; Heyman, Jefri (Frontiers in Plant Science, 2021)
Compared to other species, plants stand out by their unparalleled self-repair capacities. Being the loss of a single cell or an entire tissue, most plant species are able to efficiently repair the inflicted damage. Although this self-repair process is commonly referred to as “regeneration”, depending on the type of damage and organ being affected, subtle to dramatic differences in the modus operandi can be observed. Recent publications have focused on these different types of tissue damage and their associated response in initiating the regeneration process. Here, we review the regeneration response following loss of a single cell to a complete organ, emphasizing key molecular players and hormonal cues involved in the model species Arabidopsis thaliana. In addition, we highlight the agricultural applications and techniques that make use of these regenerative responses in different crop and tree species.